2021
DOI: 10.1177/0969141321998718
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of breast positioning criteria in mammographic screening: Agreement between artificial intelligence software and radiographers

Abstract: Objectives To determine the agreement between artificial intelligence software (AI) and radiographers in assessing breast positioning criteria for mammograms from standard digital mammography and digital breast tomosynthesis. Methods Assessment of breast positioning was performed by AI and by four radiographers in pairs of two on 156 examinations of women screened in Bergen, April to September 2019, as part of BreastScreen Norway. Ten criteria were used; three for craniocaudal and seven for mediolateral-obliqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Further, an image evaluation method using a DCNN for skull X-ray images [22] has been reported. The most recent attempts to evaluate mammographic breast criteria have not clari ed the quantitative values derived from traditional image processing techniques [23] . We believe that our study is the rst to address mammography breast positioning using DCNN classi cation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, an image evaluation method using a DCNN for skull X-ray images [22] has been reported. The most recent attempts to evaluate mammographic breast criteria have not clari ed the quantitative values derived from traditional image processing techniques [23] . We believe that our study is the rst to address mammography breast positioning using DCNN classi cation.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning has also been applied to positioning for X-ray examinations [21,22] . Although there are several approaches to assessing mammographic positioning using computer schemes [23] , to the best of our knowledge, there are no reports on the use of DCNN for the veri cation of optimal positioning. In this study, we propose a DCNN classi cation for the quality control and validation of positioning in mammography, in which each part of a mammogram can be detected automatically.…”
Section: Introductionmentioning
confidence: 99%
“…For CEM examinations, VBD computing was limited to the LE images. To help explain potential sources of density variability, other parameters studied for their potential association with VBD are breast thickness and compression force (both obtained from the image DICOM header), area of the compression paddle in contact with the breast [ 37 ], distance between the nipple and the posterior-edge (both determined by image analysis) [ 38 ], compression pressure calculated as the ratio between compression force and contact area, and mean glandular dose (MGD) obtained by applying the dosimetry model proposed by Dance and colleagues [ 39 , 40 , 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Volpara is developed to measure image quality as one measure, where the pectoral muscle appearance represents one out of several measures (16,22). However, a previous study made quantitative measurements of pectoral muscle angle and length to posterior nipple line and compared human versus Volpara metrics (23). That study showed adequate accuracy of the Volpara measures, especially to the level needed to observe trends within large sample sizes.…”
Section: Study Limitationsmentioning
confidence: 99%